Empowering the Rights of Persons with Disabilities in Accessing Justice in the Shariah Courts of Malaysia - Mohd Nor, Aishah; Sahri, Mardhiyyah; Mahmod, Zulzaidi; Zainudin, Ulfah Mansurah; Mohd Kusrin, Zuliza (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Persons with disabilities (PWD) face significant barriers in accessing justice in the Shariah Courts of Malaysia. Despite the existing legal frameworks designed to protect the rights of PWD, the implementation of these rights remains challenging. This study seeks (1) to analyse the status of PWD from the Islamic perspective, (2) to examine the Malaysian legal framework on the rights of PWD, (3) to explore the challenges encountered by the Shariah Courts in addressing legal proceedings involving PWD and (4) to propose recommendations for empowering the rights of PWD in accessing justice in the Shariah Courts of Malaysia. This research employs a qualitative study through library research and focus group discussion with five (5) Shariah Court officers from four (4) districts in Malaysia and examines four (4) court files. The data were analyzed using thematic analysis to identify challenges encountered by the Shariah Courts in dealing with legal proceedings involving PWD as litigants and to propose recommendations based on the challenges identified. The study reveals that the absence of a specific law addressing PWD’s rights within the Shariah Courts hinders the full effectiveness of these protections, leading to challenges in implementation. It highlights the need for improvements including the establishment of specialized Standard Operating Procedures to assist the Shariah Courts in accommodating PWDs and enhancing coordination between the Shariah Courts and PWD-related agencies to ensure the effective realization of PWDs' rights to access justice in the Shariah Courts of Malaysia.